Callous and emotional: exploring the variants of psychopathic personality in community adolescents - Alonso, Cristina; Álvarez-Voces, María; Romero, Estrella (Anales de Psicología / Annals of Psychology, 2026)
Research on callous-unemotional traits (CU) as precursors of the most chronic and severe forms of antisocial behavior in youth has significantly increased. Concurrently, growing interest has emerged in examining CU variants that may exhibit distinct etiologies and manifestations. Emotional dysregulation has been proposed as a potential feature underlying a specific CU subtype, characterized by unique determinants and correlates. Thus, the aim of this study was to identify distinct adolescent profiles based on combinations of CU and negative affect (NA), and to analyze their differential associations with personality dimensions and with indicators of behavioral and socioemotional maladjustment. Participants included 902 school-enrolled adolescents (Mage=14.89; SD=1.67), followed up one year later. Latent Profile Analysis identified five distinct profiles, including one with high CU and low NA, and two emotionally dysregulated profiles—one characterized by predominant CU and another by predominant NA. Profiles differed in basic personality traits and attachment styles. One year later, significant differences emerged in indicators of behavioral maladjustment, socioemotional well-being, and risk behaviors. Findings from this person-centered approach support the distinction between CU variants, aligning with classical conceptions of primary and secondary psychopathy. Specifically, secondary CU variants exhibit greater emotional, social, and behavioral maladjustment than the primary variant.